Evaluating Hygiene and Sanitation Practices in Pastry Equipment - Nurlena, Nurlena; Sumarsih, Umi; Dianita, Indria Angga (Journal of Business on Hospitality and Tourism, 2023)
Hygiene and sanitation in pastry production are essential to ensure food safety, maintain product quality, and build customer trust. Pastry production involves intricate tools and processes where hygiene plays a critical role in preventing contamination and ensuring safe consumption. This qualitative study examined the cleanliness and sanitation of pastry utensils of two prominent hotels in Bandung, Indonesia. Through a combination of observational assessments and semi-structured interviews, this study uncovered existing practices, identified potential vulnerabilities, and proposed targeted improvements to enhance overall equipment hygiene standards in pastry production settings. The findings are poised to contribute to the greater understanding of cleanliness and sanitation protocols’ impact on culinary productions.